The effect of product design on recycling efficiency of lithium-ion batteries through structural equation modeling and life cycle assessment - Haitao Chen; Yongxun Yang; Zhaohui Dong (Scientific Reports)
Abstract This study investigates the impact of lithium-ion battery (LIB) design characteristics on recycling efficiency through a comprehensive mixed-methods research approach. The study employs structural equation modeling (SEM) and analytic hierarchy process (AHP) methodologies, analyzing data collected through systematic expert interviews with 15 industry professionals and structured surveys of 150 battery manufacturing and recycling facilities. Through rigorous qualitative and quantitative analysis, this research examines the relationships between design complexity, material diversity, connection methods, and recycling process efficiency and overall recycling performance. The research methodology combines in-depth interviews, expert consultations, and statistical analysis to ensure robust findings. Data sources include primary data from industry surveys, expert interviews, and secondary data from technical documentation and recycling facility reports, providing a comprehensive foundation for the analysis. The research compares recycling efficiency across different battery types, including traditional designs, cell-to-pack (CTP), and cell-to-body (CTB), utilizing multi-group analysis. Through life cycle cost analysis and environmental impact assessment, the study quantifies the potential economic and ecological benefits of optimized designs. Results indicate that while optimized LIB designs may increase initial production costs, they significantly enhance recycling efficiency, reduce total lifecycle costs, and minimize environmental impacts. SEM analysis reveals that design characteristics indirectly influence overall recycling performance by affecting recycling process efficiency. Multi-group analysis demonstrates the superior recyclability of CTP and CTB designs compared to traditional configurations. The study also evaluates the improvement potential for recycling efficiency across various materials, providing a basis for optimizing recycling strategies. This research offers valuable insights for battery design, recycling technology innovation, and policy formulation, emphasizing the importance of incorporating recyclability considerations in LIB development. It contributes significantly to advancing the energy storage industry towards a circular economy model.